1987
DOI: 10.1017/s000335610001878x
|View full text |Cite
|
Sign up to set email alerts
|

Wilting of herbage prior to ensiling: effects on conservation losses, silage fermentation and growth of beef cattle

Abstract: A sward of perennial ryegrass was either directly ensiled at 181 g dry matter (DM) per kg fresh weight with formic acid applied at 3-6 1/t fresh material or wilted for 65 h to achieve a DM concentration of 407 g DM per kg. Physical and respiration loss were measured in the field and losses during ensiling were estimated from buried bags. The silages were offered to 58 British Friesian steers, initially 3 months of age and 101 kg live weight (LW). Ten steers were allocated to an initial slaughter group and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

1988
1988
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
0
7
0
2
Order By: Relevance
“…However, if such effects are real it is not clear whether they reflect a reduced efficiency of utilization of ME for milk production ( k l ), a change in the partitioning of ME for production between body tissue and milk energy output, or an effect of protein quality in the ensiled material. A number of authors of studies used in the present data set have suggested that k l is reduced because of wilting, although Castle and Watson (1984), Zimmer and Wilkins (1984), Charmley and Thomas (1987) and Peoples and Gordon (1989) reported no influence of wilting on the efficiency of ME utilization. In addition, in most studies, the liveweight change data would suggest that wilting does not influence the partitioning of nutrients between milk yield and body reserves ( Rohr and Thomas, 1984).…”
Section: Discussionmentioning
confidence: 56%
“…However, if such effects are real it is not clear whether they reflect a reduced efficiency of utilization of ME for milk production ( k l ), a change in the partitioning of ME for production between body tissue and milk energy output, or an effect of protein quality in the ensiled material. A number of authors of studies used in the present data set have suggested that k l is reduced because of wilting, although Castle and Watson (1984), Zimmer and Wilkins (1984), Charmley and Thomas (1987) and Peoples and Gordon (1989) reported no influence of wilting on the efficiency of ME utilization. In addition, in most studies, the liveweight change data would suggest that wilting does not influence the partitioning of nutrients between milk yield and body reserves ( Rohr and Thomas, 1984).…”
Section: Discussionmentioning
confidence: 56%
“…Research from the 1980s and before suggested that intake of silage was increased by wilting (e.g., Marsh 1979;Zimmer and Wilkins 1984). However, in many of those studies animal performance was not improved (Charmley and Thomas 1987) and this was attributed to reduced digestibility in wilted compared with unwilted silage, and reduced efficiency of energy utilization (Unsworth and Gordon 1985). From other work, particularly with inoculant-treated silages, this digestibility effect now seems to be due to an increase in digestibility of more extensively fermented silages rather than a reduction in digestibility due to wilting (Cushnahan and Gordon 1995).…”
Section: Restricting Fermentation Through Wiltingmentioning
confidence: 99%
“…Fresh forage is occasionally ensiled directly to avoid inclement weather, accelerate the harvesting process and improve uniformity of regrowth by eliminating windrows on the ground. Extensive protein degradation during fermentation has been documented in many legumes (McKersie, 1985; Charmley and Thomas, 1987; Albrecht and Muck, 1991). This may reduce the efficiency with which N is utilized by ruminants (Waldo, 1985) and increases the risk of environmental contamination, as excess N is excreted in urine (Tamminga, 1992).…”
Section: Introductionmentioning
confidence: 99%